OLIVER, CHRIS. Introducción a RDA: guía básica. London: Facet Publishing, 2010, 117 págs. ISBN: 978-0-8389-3594-1. - Herrero Pascual, Por Cristina (Anales de Documentación, 2011)
OLIVER, CHRIS. Introducción a RDA: guía básica. London: Facet Publishing, 2010, 117 págs. ISBN: 978-0-8389-3594-1.